Poverty alleviation and food security strategies in the Caribbean : a policy dialogue (CFNI KingstonJM, 2007)
Highlights lessons learned from food and nutrition and poverty alleviation programmes. Deals with ways of preventing food insecurity and improving health. Focuses on public policy for enhancing regional food and nutrition security.
Additional copy located in the Office of the Secretary-General